1996
DOI: 10.1051/jp4:1996521
|View full text |Cite
|
Sign up to set email alerts
|

Field - and Photoassisted Field Emission Studies of Calcium Fluoride Coated Silicon Tips

Abstract: Measurements of field emission current-voltage and Fowler-Nordheim characteristics of Si tips covered by 100 nm-thick Ca& epitaxial layers have been for the first time performed. It was found that in spite of dielectric nature of the coating, the tips demonstrate high emissivity comparable with the diamond coated tips. Results of high resolution photoassisted field emission investigations of C W S i structures are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…The tip potential was insufficient to cause field emission from the nanotip, the photoelectric current being found to be practically independent of tip potential and to depend on the radiation intensity in a quadratic fashion, as shown in Figure . These experimental observations unambiguously point to the fact that the photoelectron images of the tips are due to the nonresonance two-photon photoemission from the diamond coatings under the effect of femtosecond laser pulses with a quantum energy of 3.02 eV (and not to the, for instance, laser-assisted field emission from the diamond, because in that case the dependence of photocurrent on the tip potential would be much sharper; compare with data presented, for example, in ref ). Such a conclusion corresponds quite well to the previous works devoted to external photoelectric effect from the diamond, where a photoemission threshold value of 5.5 eV was determined, as well as to the following known data: the band gap E g value of the diamond is equal to 5.5 eV and a negative electron affinity χ value for some crystallographic planes of diamond was reported. , It is known also that an electron affinity value for the diamond depends critically on the nature of crystallographic plane and the concrete conditions on this plane and can be varied in a rather broad range, at least from −2.2 to +0.8 eV .…”
Section: Photoelectron Images Of Needle Tips and Their Analysissupporting
confidence: 79%
See 1 more Smart Citation
“…The tip potential was insufficient to cause field emission from the nanotip, the photoelectric current being found to be practically independent of tip potential and to depend on the radiation intensity in a quadratic fashion, as shown in Figure . These experimental observations unambiguously point to the fact that the photoelectron images of the tips are due to the nonresonance two-photon photoemission from the diamond coatings under the effect of femtosecond laser pulses with a quantum energy of 3.02 eV (and not to the, for instance, laser-assisted field emission from the diamond, because in that case the dependence of photocurrent on the tip potential would be much sharper; compare with data presented, for example, in ref ). Such a conclusion corresponds quite well to the previous works devoted to external photoelectric effect from the diamond, where a photoemission threshold value of 5.5 eV was determined, as well as to the following known data: the band gap E g value of the diamond is equal to 5.5 eV and a negative electron affinity χ value for some crystallographic planes of diamond was reported. , It is known also that an electron affinity value for the diamond depends critically on the nature of crystallographic plane and the concrete conditions on this plane and can be varied in a rather broad range, at least from −2.2 to +0.8 eV .…”
Section: Photoelectron Images Of Needle Tips and Their Analysissupporting
confidence: 79%
“…The absence of the clear structure in the images can be associated with the anomalously high photoelectron escape depth l esc for the calcium fluoride: in ref 24 it was reported that such a depth can attain the value of 260 nm. (High emissive characteristics of Si:CaF 2 nanotips 15 are also consistent with such rather high electron escape depth values.) Thus, practically all defects containing a calcium fluoride coating with a thickness of 50-100 nm can contribute to the observed photoelectron images.…”
Section: Photoelectron Images Of Needle Tips and Their Analysissupporting
confidence: 68%
“…5. And lastly, the good emission properties of the CaF 2 /Si structure has recently been demonstrated in the experiment [4].…”
Section: Discussion and Summarymentioning
confidence: 84%
“…Besides, the control voltage for such tip emitters is rather high (about 100 V). Some researchers use diamond-like films that contain nanoscale crystalline structure as the electron source [2], or use diamond and other coatings of the sharp tips to improve the emission properties of the tips [3,4].…”
Section: Introductionmentioning
confidence: 99%